Chronic Disseminated Salmonellosis in a Patient With Interleukin-12p40 Deficiency. Issue 1 (January 2018) - Alaki, Emadia Mohammad; Aljobair, Fahad; Alaklobi, Faisal; Al Shamrani, Mobarak; Al-Zahim, Fahad; Dongues, Aziza; Casanova, Jean-Laurent
Abstract : Interleukin (IL)-12 is composed of p35 and p40 subunits; in this case, IL-12p40 deficiency is a rare genetic etiology of Mendelian susceptibility to mycobacterial disease. Salmonellosis has been reported in almost half of these patients and mostly present in recurrent extraintestinal form. In this report, we described an 18-month-old boy with absence of IL-12p40 production suffering from chronic disseminated nontyphoidal salmonellosis. To the best of our knowledge, this is the first-reported case.